Understanding Consumers Intention toward Electric Vehicles Through the SOR Framework - Ariyanto, Hepy Hefri; Purwianti, Lily; Steven; Changbo, Liu (Universitas Medan Area, 2025)
This study investigated the determinants of electric vehicle (EV) purchase intentions in Batam, Indonesia, utilizing the Stimulus–Organism–Response (SOR) framework. We examined how four external stimuli government support, perceived monetary benefits, technology orientation, and perceived risk influence consumer attitude and subsequent purchase intention. Data collected from 356 potential EV adopters via purposive sampling were analyzed using PLS-SEM. The results indicate that government support, per-ceived monetary benefits, and technology orientation significantly enhance consumer attitude, which, in turn, strongly strengthens purchase intention. This confirms attitude as a central psychological me-chanism mediating the SOR process in EV adoption. However, perceived risk was found to have no significant effect on either attitude or intention, suggesting that a strong policy-supported environment in Batam might mitigate consumer concerns regarding EV technology. These findings validate the SOR framework's application in understanding EV adoption in developing markets. Practically, the study em-phasizes that accelerating the transition to sustainable mobility requires continued government fiscal incentives, sustained technological advancements, and effective public awareness campaigns. By strengthening these positive stimuli, policymakers and practitioners can significantly enhance consumer readiness and contribute to national green-transportation goals.